2009
DOI: 10.1007/s10705-009-9252-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mulch, N fertilizer, and plant density on wheat yield, wheat nitrogen uptake, and residual soil nitrate in a dryland area of China

Abstract: Understanding mulching influences on nitrogen (N) activities in soil is important for developing N management strategies in dryland. A 3 year field experiment was conducted in the Loess Plateau of China to investigate the effects of mulching, N fertilizer application rate and plant density on winter wheat yield, N uptake by wheat and residual soil nitrate in a winter wheat-fallow system. The split plot design included four mulching methods (CK, no mulch; SM, straw mulch; FM, plastic film mulch; CM, combined mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
75
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(89 citation statements)
references
References 39 publications
13
75
1
Order By: Relevance
“…2). A similar result was also reported by Gao et al (2009), who found that wheat N accumulation was markedly increased under FM conditions. Crop N accumulation is closely related to plant growth rate and to environmental conditions, such as soil water and nutrient availability.…”
Section: Discussionsupporting
confidence: 90%
“…2). A similar result was also reported by Gao et al (2009), who found that wheat N accumulation was markedly increased under FM conditions. Crop N accumulation is closely related to plant growth rate and to environmental conditions, such as soil water and nutrient availability.…”
Section: Discussionsupporting
confidence: 90%
“…This may reduce the availability of soil mineral N and may require an increasing in N fertilisation (Morell et al, 2011). Few studies indicate that slightly higher doses of fertiliser are required to achieve significant yields in winter wheat in presence of a layer of surface residues (Gao et al, 2009), especially under long-term periods (>10 years) of CA adoption.…”
Section: Introductionmentioning
confidence: 99%
“…Film mulch has increased soil microbial biomass and activity in wheat (Li et al 2004) and flooded rice (Oryza sativa L.) fields (Li et al 2006). Increased soil mineral nitrogen (N) has been observed in film-mulched wheat cropping (Gao et al 2009). However, despite being widely practiced, there is a lack of knowledge on changes in soil biological properties and nutrient status associated with improved soil temperatures and reduced evaporation under film mulching (Gan et al 2013).…”
Section: Introductionmentioning
confidence: 99%